Closing the gap: Raising medical professionals' transgender awareness and medical proficiency through pharmacist-led education - Ardsley P. Congdon III, PharmD, BCPS, BCPP; Kathryn Tiene, PharmD; Cristofer Price, PharmD, BCPP; Robert L. Dufresne, PhD, PhD, BCPS, BCPP (Mental Health Clinician, 2021)
Introduction: Patients who are transgender have unique population-specific needs and risk factors. Nationwide surveys of health profession school administrators indicate a gap in coverage of lesbian, gay, bisexual, and transgender health content in their curricula. To address this gap, a pharmacist-developed transgender–health care focused seminar was presented to medical professionals, trainees, and students accompanied by a novel education assessment scale. Methods: The seminar was presented by a psychiatric pharmacy resident to health care professionals and trainees in various settings. Subjects covered during the seminar included terminology, diagnostic criteria and prevalence of gender dysphoria, nonhormonal treatment, gender-affirming hormone therapy, and other considerations. The Trans* Health Education Evaluation Scale (THEES) was developed to assess participants' self-perceived proficiency regarding care of patients who are transgender immediately before and after attending a seminar. Total scale scores were compared preseminar and postseminar using a repeated-measures t-test, and sign tests with Bonferroni correction were used for individual scale items. Psychometric properties of this scale were examined. Results: Five seminars were given, and a total of 100 scales were completed by health care–associated workers and students. The majority of participants were in the pharmacy or medical professions. Attending 1 seminar significantly improved THEES total and individual item scores (P<.001). Additionally, 90% of participants felt the seminar was directly applicable to their practice, and 84% felt more confident in providing care to patients who are transgender. Discussion: A single, pharmacist-led, trans health-focused education session significantly improved the confidence level and self-perceived proficiency of health care-associated personnel as measured by THEES.